Effects of herbage ingestion on the digestion site and nitrogen balance in heavy Iberian pigs fed on an acorn-based diet - Garcia-Valverde, R; Nieto, R; Lachica, M; Aguilera, J F (LIVESTOCK SCIENCE, 2007)
We conducted two experiments in heavy-weight Iberian pigs to determine: a) the effect of lysine or protein addition - the former as L-lysine-HCl, the latter by fresh cut herbage supplementation - on protein deposition when they were fed on holm-oak acorns; b) the digestibility of energy and nutrients in acorns and freshly cut, mixed herbage; and c) a possible change in the partition of digestion along the gastro-intestinal tract of the pigs fed on acorns with the inclusion of herbage. In Experiment 1, carried out in eight cannulated pigs, the daily intake of acorns reached 44.9 g DM/kg(0.75) BW and the addition of 0.58 g L-lysine/kg of whole acorns failed to alter N retention significantly (P > 0.05). We obtained high coefficients for the apparent total-tract digestibility of dry matter (ApDM(tt), 0.84) and organic matter (ApOM(tt), 0.86) and of gross energy (ApGE(tt), 0.84) in whole acorns. The corresponding ileal values were 0.71, 0.74 and 0.74. The N balance was on average - 1.08 g/day. In Experiment 2, fresh herbage containing principally legumes was offered to six cannulated Iberian pigs of 140 kg either as a single feed (13.7 g DM/kg(0.75) BW) or as a supplement to acorns (28.4 g DM/kg(0.75) BW; in this case the herbage accounted for 22% of the daily DM intake). The apparent ileal digestibilities of OM and GE for herbage accounted for 70 to 77% of the values observed at total-tract level (0.65 and 0.64 respectively). N retention reached 4.21 g/day. Average ApDM(tt), ApOM(tt) and ApGE(tt) in the herbage/whole-acorn mixture were slightly above 0.74. The intake of freshly cut herbage as complementary feed to acorns resulted in a significant transference of digesta from the small intestine to the hind gut together with a substantial decrease in ileal digestibility of nutrients and energy (P < 0.001) and a moderate decline in digestibility at throughout the whole tract (P < 0.01-P < 0.001). On the other hand, the apparent digestibility of total N increased (P < 0.001) and 31% of the N apparently digested was retained in the body of the pigs. We also observed a substantial decrease in the precaecal digestion of the DM (P < 0.01), OM (P < 0.01) and GE (P < 0.05) in acorn kernels. We concluded that the main contribution of herbage to the overall nutrient supply to the grazing Iberian pig would rely upon the provision of amino acid N and also of available minerals, both present in low quantities in acorns. (C) 2007 Elsevier B.V All rights reserved.
Keywords: acorns; digestibility; energy value; herbage; iberian pig

Amino acid availability and energy value of acorn in the Iberian pig - Aguilera, J F; Nieto, R; Rivera, M; García, M A (Livestock Production Science, 2002)
Two experiments have been performed to determine amino acid digestibility and energy value of acorn (Quercus rotundifolia L.) for Iberian pigs. In experiment 1 ileal digestibility of amino acids was determined in ﬁve ileum-cannulated growing pigs fed whole ground acorn. An estimation of endogenous protein losses was carried out by feeding a protein-free diet, added (180 g/kg) or not with acorn hulls. True ileal digestibility of all essential amino acids measured was high (0.798–1.03) except for arginine (0.523), lysine (0.601), isoleucine (0.760), leucine (0.777) and phenylalanine (0.716). The average value for the digestibility of the sum of amino acids was 0.664. Lysine was the ﬁrst limiting amino acid compared with the amino acid proﬁle of the ideal protein for pigs. In experiment 2, total tract digestibility of nutrients and N balance were determined in ﬁve, non-cannulated pigs offered whole acorns. High coefﬁcients for the apparent total tract digestibility of dry matter (ApDM) (0.830) and energy metabolizability (ME/GE; 0.805) were found. ME content for acorn kernel was 16.6 MJ/kg DM, while the apparent total tract digestibility of total N (ApTN) was as low as 0.408. However, a positive N retention was observed (3.7 g/day). Comparing experiments 1 vs. 2, inclusion of acorn hulls resulted in a marked decrease in DM intake, ApTN and in N retention (25.1 g/day, in total tract data from experiment 1). The negative effects of acorn hulls on protein digestibility and N balance were corroborated in rats given similar amounts of either whole ground acorn or ground acorn kernel. Dietary supplementation with lysine is proposed to achieve a higher efﬁciency of protein accretion in the Iberian pig when fed on acorn.
Keywords: acorn; amino acids; energy value; pig-feeding and nutrition; protein quality

The voluntary intake and rumen digestion by grazing goats and sheep of a low-quality pasture from a semi-arid land - Alcaide, E M; García, M A; Aguilera, J F (Livestock Production Science, 1997)
An experiment was carried out in late autumn with goats and wethers fitted with permanent ruminal cannulae, grazing in a semi-arid area of South Spain. Shrubs were the most available plant species, although natural vegetation also included trees and grasses. In general, the dominant species of the available vegetation accounted for the highest proportion in the selected diet. Similar proportion and species of grasses were found in the pasture selected by goats and wethers, whereas interspecies differences were observed regarding the selection of shrubs and tree species. Crude protein content was similar in selected diets by goats and sheep, but a higher unavailable N proportion was found for sheep (27.1 and 30.0% of total N for goats and sheep, respectively). Digestibility of forage selected was higher for goats than for wethers. Voluntary intake was significantly (P < 0.05) higher in goats than in sheep; the metabolizable energy intake for goats was higher than their maintenance requirements but failed to meet maintenance needs for wethers. Fermentative rumen activity was moderate and similar for goats and sheep. No interspecies differences were found in rumen fermentation parameters except for molar proportions of acetic and propionic acid and for acetic/propionic ratio, which were significantly higher in wethers. The degradation rate tended to be faster in goats, whereas potential and effective degradability tended to be similar in goats and sheep.
Keywords: Goats; intake; rumen fermentation; semi-arid land; Sheep